Evaluation of an attention deficit hyperactivity disorder service: a questionnaire survey and audit. (29th September 2015) - Patel, N; Palanivel, V; Anjay, MAP; Goodwin, A
Abstract : Aims: Attention deficit hyperactivity disorder (ADHD) is being increasingly diagnosed and there is a general perception that service provision in many areas has not kept up with the increased demand. The service in our region, catering to a large population, comprises of a community paediatrician, ADHD nurse and a medical officer. The National Institute for Health and Clinical Excellence (NICE) has recently issued guidelines for the diagnosis and management of ADHD, which was available as a prepublication draught at the time of this study. The authors aimed to: ▸ Assess knowledge of parents of children with ADHD about some key issues in the management. ▸ Measure parental satisfaction with the service ▸ Audit our practice against some of the key recommendations provided in the prepublication draught of the ADHD guidelines issued by NICE Methods: All parents of children who attended the ADHD clinics during a period of one month were given a printed questionnaire. They were requested to complete and return them on the same day. The data were then analysed. Results: Four ADHD clinics were conducted in the month of the survey. There were a total of 51 patients. All the parents returned the questionnaires. 100% of the parents agreed that non-pharmacologic options were discussed before starting medications, as recommended by NICE. Most of them were also aware of the common side-effects. 84% revealed that they were advised regarding resources like internet and books, as recommended by NICE. Though 97% of the parents had informed schools about the diagnosis, only 65% were happy with the way the schools were dealing with their children. Overall, 97% of the parents felt that the ADHD clinics were useful. Conclusions: Our ADHD service is compliant with some major aspects of the NICE guidelines. In spite of limited resources, the service is well organised and satisfactory to most parents.